2012
DOI: 10.1007/s13318-012-0097-6
|View full text |Cite
|
Sign up to set email alerts
|

Individualization of a pharmacokinetic model by fractional and nonlinear fit improvement

Abstract: This study presents application of a new linear and nonlinear fractional derivative two compartmental model to the evaluation of individual pharmacokinetics. In the model, the integer order derivatives are replaced by derivatives of real order. A specific nonlinear function is used for the fit improvement of a fractional derivative two compartmental model with the mass balance conservation. The agreement of the values predicted by the proposed model with the values obtained through experiments with bumetanide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 27 publications
1
4
0
2
Order By: Relevance
“…In humans, the PBPK model of bumetanide was verified in healthy adult volunteers using intravenous data (Table , Figure ). The simulated output demonstrated a two‐compartment profile, consistent with published pharmacokinetic models (Jullien et al, ; Marcantonio et al, ; Popovic et al, ). Simulations of intravenous bolus injections generated reasonable pharmacokinetic predictions of area under the concentration–time curve (AUC) (0.71–1.15), peak plasma concentration (C max ) (0.62–1) and time to reach peak plasma concentration (t max ) (0.5–1) as shown by the predicted/observed ratios (Table ) and concentration–time profiles overlaid with observed data (Figure ).…”
Section: Resultssupporting
confidence: 83%
“…In humans, the PBPK model of bumetanide was verified in healthy adult volunteers using intravenous data (Table , Figure ). The simulated output demonstrated a two‐compartment profile, consistent with published pharmacokinetic models (Jullien et al, ; Marcantonio et al, ; Popovic et al, ). Simulations of intravenous bolus injections generated reasonable pharmacokinetic predictions of area under the concentration–time curve (AUC) (0.71–1.15), peak plasma concentration (C max ) (0.62–1) and time to reach peak plasma concentration (t max ) (0.5–1) as shown by the predicted/observed ratios (Table ) and concentration–time profiles overlaid with observed data (Figure ).…”
Section: Resultssupporting
confidence: 83%
“…Clinical evidences have shown that, in AIS patients, high NLR levels are associated with increased infarct volume and mortality (Celikbilek, Ismailogullari, & Zararsiz, 2014;Gökhan et al, 2013;Tokgoz et al, 2013). Furthermore, NLR is a predictor of recurrent ischemic stroke and 90-day poor functional outcome in AIS patients receiving endovascular stroke therapy or IVT or antiplatelet medications (Brooks et al, 2014;Duan et al, 2018;Malhotra et al, 2018;Qun et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In practice, non-linearities, anomalous diffusion, fractional-order kinetics, diffusion accross fractal manifolds, synergetic and competitive action and a great many other factors render this approach not applicable (see Dokoumetzidis and Macheras [2008]). Recently, a significant number of relevant publications has emerged; see Popović et al [2012], Verotta [2010a,b], Pereira [2010], Dokoumetzidis et al [2010b], Popović et al [2010].…”
Section: Motivationmentioning
confidence: 99%